2017
DOI: 10.15376/biores.12.2.3289-3302
|View full text |Cite
|
Sign up to set email alerts
|

Superhydrophobic Coating of European Oak (Quercus robur), European Larch (Larix decidua), and Scots Pine (Pinus sylvestris) Wood Surfaces

Abstract: Plant surfaces provide an unlimited source of systems for the protection of their surface against the outer environment. These systems have continuously improved over the last 400 million years of evolution. Two of the most fascinating properties of these systems are superhydrophobicity and the self-cleaning ability of several plant species. These properties are most often achieved due to the hierarchical structure of the surface in combination with a deposited blend of epicuticular waxes. In this study, a lay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Based on the results, it can be concluded that the hydrophobic layers and the oil coating significantly increase the hydrophobicity of natural wood surfaces [14,77]. However, the increase in hydrophobicity after coating application [15,50,52] does not necessarily indicate long-term functionality during exposure to weathering (Figures 6 and 7). In general, the use of hydrophobic layers can only be recommended for sheltered wood (i.e., without leaching of extractives by water), which can lead to easier maintenance and cleaning during use.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Based on the results, it can be concluded that the hydrophobic layers and the oil coating significantly increase the hydrophobicity of natural wood surfaces [14,77]. However, the increase in hydrophobicity after coating application [15,50,52] does not necessarily indicate long-term functionality during exposure to weathering (Figures 6 and 7). In general, the use of hydrophobic layers can only be recommended for sheltered wood (i.e., without leaching of extractives by water), which can lead to easier maintenance and cleaning during use.…”
Section: Resultsmentioning
confidence: 96%
“…This could be potentially prevented using hydrophobic self-cleaning coatings in combination with UV stabilization of the underlying wood. Although more studies have been done to investigate the possibilities of wood surface hydrophobic modification [15,[50][51][52], their long-term efficiency during outdoor exposure should also be considered.…”
Section: Introductionmentioning
confidence: 99%
“…This problem was broadly investigated in the research project Interaction of Man and Wood in 2013. Many collaborations with other researchers and institutions were done, including the development of super-hydrophobic surface finishes [4], the investigation of wood’s natural interaction with microorganisms according to the different surface finishings [5,6], and a comprehensive study of the suitability of wood in health care facilities. These were finally applied as solutions for hospital interiors and later into an in situ experiment.…”
Section: Introductionmentioning
confidence: 99%
“…Plant‐based waxes are used, allowing for large‐scale fabrication of nanostructured superhydrophobic coatings from available bio‐resources. [ 61 ] We investigate the influence of solvent and temperature on the topographies generated through the crystallization process and the effect on the corresponding surface wettability mode. We perform a series of analytical measurements to characterize the structure, melting temperature, and composition of the various wax crystals produced through the cooling and evaporation of diverse solvents.…”
Section: Introductionmentioning
confidence: 99%